Comparison of Immediate With Delayed Stenting Using the Minimalist Immediate Mechanical Intervention Approach in Acute ST-Segment–Elevation Myocardial Infarction: The MIMI Study. (March 2016) - Belle, Loic; Motreff, Pascal; Mangin, Lionel; Rangé, Grégoire; Marcaggi, Xavier; Marie, Antoine; Ferrier, Nadine; Dubreuil, Olivier; Zemour, Gilles; Souteyrand, Géraud; Caussin, Christophe; Amabile, Nicolas; et al.
Abstract : Background—: Delayed stent implantation after restoration of normal epicardial flow by a minimalist immediate mechanical intervention aims to decrease the rate of distal embolization and impaired myocardial reperfusion after percutaneous coronary intervention. We sought to confirm whether a delayed stenting (DS) approach (24–48 hours) improves myocardial reperfusion, versus immediate stenting, in patients with acute ST-segment–elevation myocardial infarction undergoing primary percutaneous coronary intervention. Methods and Results—: In the prospective, randomized, open-label minimalist immediate mechanical intervention (MIMI) trial, patients (n=140) with ST-segment–elevation myocardial infarction ⩽12 hours were randomized to immediate stenting (n=73) or DS (n=67) after Thrombolysis In Myocardial Infarction 3 flow restoration by thrombus aspiration. Patients in the DS group underwent a second coronary arteriography for stent implantation a median of 36 hours (interquartile range 29–46) after randomization. The primary end point was microvascular obstruction (% left ventricular mass) on cardiac magnetic resonance imaging performed 5 days (interquartile range 4–6) after the first procedure. There was a nonsignificant trend toward lower microvascular obstruction in the immediate stenting group compared with DS group (1.88% versus 3.96%; P =0.051), which became significant after adjustment for the area at risk ( P =0.049). Median infarct weight, left ventricular ejection fraction, and infarct size did not differ between groups. No difference in 6-month outcomes was apparent for the rate of major cardiovascular and cerebral events. Conclusions—: The present findings do not support a strategy of DS versus immediate stenting in patients with ST-segment–elevation infarction undergoing primary percutaneous coronary intervention and even suggested a deleterious effect of DS on microvascular obstruction size. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01360242. Abstract : Supplemental Digital Content is available in the text.